Determining Reliability Parameters for a Closed-Cycle Small Combined Heat and Power Plant; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Vysokomorny (Vysokomorniy) V. S. Vladimir Sergeevich (2016, 2016)
Title screen